VD_FINDINFO Décision / 2011 / 692 vom 30. September 2011 - VD Tribunal cantonal (2011)
HONNEUR, INFRACTIONS CONTRE L'HONNEUR, CLASSEMENT DE LA PROCÉDURE | 310 CPP (CH), 393 al. 1 let. a CPP (CH), 393 CPP (CH)